Controls on Carbonate System Dynamics in a Coastal Plain Estuary: A Modeling Study. Issue 1 (12th January 2019) - Shen, Chunqi; Testa, Jeremy M.; Li, Ming; Cai, Wei‐Jun; Waldbusser, George G.; Ni, Wenfei; Kemp, W. Michael; Cornwell, Jeffrey; Chen, Baoshan; Brodeur, Jean; Su, Jianzhong
Abstract: The study of acidification in Chesapeake Bay is challenged by the complex spatial and temporal patterns of estuarine carbonate chemistry driven by highly variable freshwater and nutrient inputs. A new module was developed within an existing coupled hydrodynamic‐biogeochemical model to understand the underlying processes controlling variations in the carbonate system. We present a validation of the model against a diversity of field observations, which demonstrated the model's ability to reproduce large‐scale carbonate chemistry dynamics of Chesapeake Bay. Analysis of model results revealed that hypoxia and acidification were observed to cooccur in midbay bottom waters and seasonal cycles in these metrics were regulated by aerobic respiration and vertical mixing. Calcium carbonate dissolution was an important buffering mechanism for pH changes in late summer, leading to stable or slightly higher pH values in this season despite persistent hypoxic conditions. Model results indicate a strong spatial gradient in air‐sea CO2 fluxes, where the heterotrophic upper bay was a strong CO2 source to atmosphere, the mid bay was a net sink with much higher rates of net photosynthesis, and the lower bay was in a balanced condition. Scenario analysis revealed that reductions in riverine nutrient loading will decrease the acid water volume (pH < 7.5) as a consequence of reduced organic matter generation and subsequent respiration, while bay‐wide dissolved inorganic carbon (DIC) increased and pH declined under scenarios of continuous anthropogenic CO2 emission. This analysis underscores the complexity of carbonate system dynamics in a productive coastal plain estuary with large salinity gradients. Key Points: A new carbonate chemistry module was developed to understand the underlying processes controlling variations in the carbonate system Model results revealed that seasonal cycles of acidification in midbay bottom waters was regulated by aerobic respiration and vertical mixing Scenario analysis revealed that reductions in riverine nutrient loading will decrease the acid water volume